2005
DOI: 10.1038/sj.ijir.3901329
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural comparison of penile cavernous tissue between hypertensive and normotensive rats

Abstract: Our aim was to compare the ultrastructure of penile cavernous tissue in the spontaneous hypertensive rat (SHR) and normotensive rat, and study the relation of blood pressure with erectile function. After injection of apomorphine (APO), penile erectile frequency in 16-week-old SHR (group A) and Wistar-Kyoto rat (WKY) (group B) was observed and noted. The ultrastructure of the penile cavernous tissue was studied by scanning electron microscope and transmission electron microscope. The mean blood pressures were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
3
35
0
2
Order By: Relevance
“…This condition leads to vascular stiffness, compromises cavernous SM vasodilatation, and modifies the cell-cell communication. The sinusoidal spaces will become narrower, less able to retain blood, and thus the inflow of blood into cavernous spaces to elevate the pressure within the penis decreases (Jiang et al 2005) contributing to veno-occlusive ED (Shen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This condition leads to vascular stiffness, compromises cavernous SM vasodilatation, and modifies the cell-cell communication. The sinusoidal spaces will become narrower, less able to retain blood, and thus the inflow of blood into cavernous spaces to elevate the pressure within the penis decreases (Jiang et al 2005) contributing to veno-occlusive ED (Shen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Ageing-related erectile dysfunction (ED) is primarily due to corporal veno-occlusive dysfunction (CVOD) [1,2], as a result of a loss of the corporal smooth muscle cells (SMCs) together with excessive collagen deposition within the corpora, as shown both in man [3][4][5] and rat models [6][7][8][9][10][11][12][13][14]. It has been hypothesized that this histological alteration is due to oxidative stress triggered by the release of profibrotic factors such as reactive oxygen species, TGF-β 1 , plasminogen activator inhibitor-1, and others, that not only lead to collagen accumulation but also to an increase in apoptosis and a reduction in corporal SMC proliferation [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that this histological alteration is due to oxidative stress triggered by the release of profibrotic factors such as reactive oxygen species, TGF-β 1 , plasminogen activator inhibitor-1, and others, that not only lead to collagen accumulation but also to an increase in apoptosis and a reduction in corporal SMC proliferation [6][7][8][9][10][11][12][13][14]. As such, it appears as if the ideal way to treat this ageing-related ED would be to reverse or prevent these changes, because such an approach has the potential to become a curative rather than a palliative intervention for this form of ED.…”
Section: Introductionmentioning
confidence: 99%
“…This second study also found that the elastic tissue within the corporeal bodies showed an inverse relationship with blood pressure. 14 Although changes in collagen content have been found in animal models of ED, human studies do not show such a clear relationship. 15 Fibrosis and increased collagen content do not appear to be as strong a predictor of erectile function as smooth muscle function or smooth muscle content.…”
Section: Pathophysiology Of Erectile Dysfunctionmentioning
confidence: 98%